Comparison of the Effectiveness of Acceptance and Commitment Therapy and Meaning-Centered Therapy Based on Rumi’s Thoughts on Pain Catastrophizing and Distress Tolerance in Men with Gastric Cancer - Ansari , Kosar; Noruzi , Asghar; Khalili , Gholamreza (KMAN Counseling & Psychology Nexus, 2025)
The aim of the present study is to compare the effectiveness of Acceptance and Commitment Therapy (ACT) and Meaning-Centered Therapy (MCT) based on Rumi’s thoughts on pain catastrophizing and distress tolerance in men with gastric cancer. The research method was quasi-experimental, conducted using a pretest-posttest design with two experimental groups and a control group, along with a follow-up phase. The statistical population of the study included all men with gastric cancer at Imam Khomeini Hospital in Sari during the years 2023-2024. Among the statistical population, 45 individuals were selected through convenience sampling and assigned to three groups. The research instruments included the Pain Catastrophizing Questionnaire (Rahmati et al., 2017) and the Distress Tolerance Scale (DTS-15) (Simons & Gaher, 2005). To analyze the hypotheses, assumption tests (Shapiro-Wilk, Mbox, Cook’s distance) and multivariate analyses using repeated measures analysis of variance and the Bonferroni correction test were employed. The results indicated that Meaning-Centered Therapy based on Rumi’s thoughts had a greater effect on improving the components of pain catastrophizing (magnification and rumination). Additionally, there was a significant difference in the scores of the components of distress tolerance (acceptance, absorption, evaluation, and regulation) between the Acceptance and Commitment Therapy and Meaning-Centered Therapy based on Rumi’s thoughts groups, compared with the control group (p < 0.01). However, there was no significant difference in the scores of the four components of distress tolerance between the Acceptance and Commitment Therapy group and the Meaning-Centered Therapy based on Rumi’s thoughts group.